Technology and Digital Literacy as Drivers of Student Success in an Open and Distance e-Learning Environment - Badaru, Kazeem Ajasa (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance)

(untitled) (AU Press, 2026)
This article examines the importance of technology and digital literacy to student success in an Open and Distance e-Learning (ODeL) environment. The existing literature often oversimplifies digital literacy, failing to examine how it affects a student's technological proficiency and, consequently, their success in ODeL contexts. This indicates a gap in understanding the significance of digital literacy and technology for student success in an ODeL environment. This paper employed a narrative literature review, using connectivism as the theoretical framework, to explore how digital literacy and technology are crucial to students' success in ODeL and electronically mediated environments. Connectivism emerged as a theory for the digital age, positing that technology and socialization are network phenomena that influence learning. Results demonstrate how connectivism explains the relationship between technology, digital literacy, and student success in ODeL institutions. Students from diverse backgrounds can access education anytime, from any location, given the integration of technology and digital literacy into ODeL practices, which enhances accessibility and flexibility and enriches learning experiences. It is recommended that educational policies require ODeL curricula to include digital literacy training, equipping students with the skills they need to thrive in technologically advanced learning environments. The study concludes that equitable access to technology and the development of digital literacy are imperative for students to succeed in ODeL environments and to reduce academic achievement gaps. This article advances a connectivist synthesis of technology and digital literacy functioning interdependently as cohesive drivers of student success in the ODeL context.